Effect of chronic treatment with Rosiglitazone on Leydig cell steroidogenesis in rats: In vivo and ex vivo studies - Lima Maria C; Galdino Suely L; Vieira Juliany; Peixoto Christina A; Udrisar Daniel P; Barros Cleiton D; Saraiva Karina LA; Couto Janaína A; Pitta Ivan R; Wanderley Maria I (BMC, 2010)
Abstract Background The present study was designed to examine the effect of chronic treatment with rosiglitazone - thiazolidinedione used in the treatment of type 2 diabetes mellitus for its insulin sensitizing effects - on the Leydig cell steroidogenic capacity and expression of the steroidogenic acute regulatory protein (StAR) and cholesterol side-chain cleavage enzyme (P450scc) in normal adult rats. Methods Twelve adult male Wistar rats were treated with rosiglitazone (5 mg/kg) administered by gavage for 15 days. Twelve control animals were treated with the vehicle. The ability of rosiglitazone to directly affect the production of testosterone by Leydig cells ex vivo was evaluated using isolated Leydig cells from rosiglitazone-treated rats. Testosterone production was induced either by activators of the cAMP/PKA pathway (hCG and dbcAMP) or substrates of steroidogenesis [22(R)-hydroxy-cholesterol (22(R)-OH-C), which is a substrate for the P450scc enzyme, and pregnenolone, which is the product of the P450scc-catalyzed step]. Testosterone in plasma and in incubation medium was measured by radioimmunoassay. The StAR and P450scc expression was detected by immunocytochemistry. Results The levels of total circulating testosterone were not altered by rosiglitazone treatment. A decrease in basal or induced testosterone production occurred in the Leydig cells of rosiglitazone-treated rats. The ultrastructural and immunocytochemical analysis of Leydig cells from rosiglitazone-treated rats revealed cells with characteristics of increased activity as well as increased StAR and P450scc expression, which are key proteins in androgen biosynthesis. However, a number of rosiglitazone-treated cells exhibited significant mitochondrial damage. Conclusion The results revealed that the Leydig cells from rosiglitazone-treated rats showed significant reduction in testosterone production under basal, hCG/dbcAMP- or 22 (R)-OH-C/pregnenolone-induced conditions, although increased labeling of StAR and P450scc was detected in these cells by immunocytochemistry. The ultrastructural study suggested that the lower levels of testosterone produced by these cells could be due to mitochondrial damage induced by rosiglitazone.